Analisis Mekanisme Kerja Citra Radar dalam Mengukur Curah Hujan Terhadap Produktivitas Pertanian pada Tanaman - Mayasari, Sinta; Wahyuni, Nilta; Sudarti, Sudarti; Mahmudi, Kendid; Selviandri, Indah (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2024)
The rainy season represents one of the climatic phenomena characterized by a discernible augmentation in precipitation within a given locale over a specified temporal interval, exhibiting a consistent pattern. Conversely, precipitation denotes the latent quantity of rainfall in a specific geographical area. Precipitation assumes a pivotal role in the sustenance of human livelihoods, particularly within the domains of agriculture, hydrology, and related fields. The primary objective of this research endeavor is to elucidate the mechanistic impact of observed precipitation, employing radar imagery systems, on agricultural productivity. This investigation adopts a non-experimental research methodology with a literature review paradigm. Radar imagery, functioning as a remote sensing apparatus, serves the purpose of forecasting precipitation in a designated region. The underlying principle of radar imagery entails the utilization of electromagnetic wave sensors with elongated wavelengths, thereby enabling the depiction of the potential intensity of detected precipitation by meteorological radar. Through systematic analysis, this information can be leveraged by individuals to prognosticate the growth dynamics of diverse plant species, thereby facilitating an augmentation in agricultural productivity. Keywords: Rainfall, Radar Imagery, Agricultural Productivity.